Coping mechanisms used by non-burned out and burned out workers in the family health strategy (Revista Latino-Americana de Enfermagem, 2009)
This study aimed to investigate stress coping mechanisms used by workers of 16 Family Health Strategy (FHS) teams in Santa Maria, RS, Brazil. Six workers with scores compatible with the Burnout Syndrome, identified through the Maslach Burnout Inventory, and six workers without the syndrome were interviewed in January and February 2007. In the reports' content analysis, we identified that burned out workers predominantly used individual mechanisms to cope with occupational problems, while non-burned out workers sought collective mechanisms. These findings indicate the importance of interpersonal relationships among FHS team members to cope with occupational stress and the need to develop collective strategies to prevent stress and maintain workers' health.